(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
Alternative pest control that can be done is by utilizing natural ingredients (biopesticides) one of the plants that can be used as biopesticides, namely basil leaves (Ocimum basilicum). Crocidolomia pavonana F., is one of the important pests that attack cabbage plants, this pest attacks cabbage plants from the seedling phase to the formation of the crop. The purpose of this research is expected to be a solution and source of information for cabbage farmers in carrying out effective control techniques against C. pavonana pests and safe for plants and consumer health and even the environment. This study used a completely randomized design (CRD), consisting of 5 treatments, namely extract concentrations of 15%, 25%, 35%, 45% and control, repeated 5 times. Based on the results of the study, it was shown that the biopesticide of basil leaf extract (Ocimum basilicum) was effective in controlling C. pavonana pests on cabbage plants. Where the extract concentration of 15% has caused mortality, until the best mortality was found on the fifth day of observation at the 45% extract concentration treatment, namely 58%. The results of this research certainly need to be developed because it is an environmentally friendly research and easy to apply in the field.